Ageing is a risk factor in imatinib mesylate cardiotoxicity. (6th February 2014) - Maharsy, Wael; Aries, Anne; Mansour, Omar; Komati, Hiba; Nemer, Mona
Abstract : Aims: Chemotherapy‐induced heart failure is increasingly recognized as a major clinical challenge. Cardiotoxicity of imatinib mesylate, a highly selective and effective anticancer drug belonging to the new class of tyrosine kinase inhibitors, is being reported in patients, some progressing to congestive heart failure. This represents an unanticipated challenge that could limit effective drug use. Understanding the mechanisms and risk factors of imatinib mesylate cardiotoxicity is crucial for prevention of cardiovascular complications in cancer patients. Methods and results: We used genetically engineered mice and primary rat neonatal cardiomyocytes to analyse the action of imatinib on the heart. We found that treatment with imatinib (200 mg/kg/day for 5 weeks) leads to mitochondrial‐dependent myocyte loss and cardiac dysfunction, as confirmed by electron microscopy, RNA analysis, and echocardiography. Imatinib cardiotoxicity was more severe in older mice, in part due to an age‐dependent increase in oxidative stress. Mechanistically, depletion of the transcription factor GATA4 resulting in decreased levels of its prosurvival targets Bcl‐2 and Bcl‐XL was an underlying cause of imatinib toxicity. Consistent with this, GATA4 haploinsufficient mice were more susceptible to imatinib, and myocyte‐specific up‐regulation of GATA4 or Bcl‐2 protected against drug‐induced cardiotoxicity. Conclusion: The results indicate that imatinib action on the heart targets cardiomyocytes and involves mitochondrial impairment and cell death that can be further aggravated by oxidative stress. This in turn offers a possible explanation for the current conflicting data regarding imatinib cardiotoxicity in cancer patients and suggests that cardiac monitoring of older patients receiving imatinib therapy may be especially warranted.